2009
DOI: 10.1038/emboj.2009.226
|View full text |Cite
|
Sign up to set email alerts
|

A key role for Ctf4 in coupling the MCM2-7 helicase to DNA polymerase α within the eukaryotic replisome

Abstract: The eukaryotic replisome is a crucial determinant of genome stability, but its structure is still poorly understood. We found previously that many regulatory proteins assemble around the MCM2-7 helicase at yeast replication forks to form the replisome progression complex (RPC), which might link MCM2-7 to other replisome components. Here, we show that the RPC associates with DNA polymerase a that primes each Okazaki fragment during lagging strand synthesis. Our data indicate that a complex of the GINS and Ctf4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
283
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(302 citation statements)
references
References 62 publications
(93 reference statements)
10
283
0
Order By: Relevance
“…S5C, Right)]. These results indicate that hCtf4 forms a complex with hGINS, as reported previously in yeast (22), but the human complex is less stable than the yeast Ctf4-GINS complex.…”
Section: Significancesupporting
confidence: 84%
See 3 more Smart Citations
“…S5C, Right)]. These results indicate that hCtf4 forms a complex with hGINS, as reported previously in yeast (22), but the human complex is less stable than the yeast Ctf4-GINS complex.…”
Section: Significancesupporting
confidence: 84%
“…Weaker hCMG binding was detected with the N (WD + SepB) domains, whereas the WD, SepB, or HMG domain alone failed to bind the hCMG complex. Previous reports indicated that the budding yeast SepB domain alone mediated an interaction between Ctf4 and GINS (22), suggesting that the HMG domain of higher eukaryotic Ctf4 may have additional binding sites in the CMG complex important for the stability of the hCtf4-CMG complex.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…On its turn, the Pol α/primase complex is anchored to the CMG helicase by the conserved Ctf4 replication factor, which acts as a bridge between the GINS component of the helicase and the catalytic subunit of Pol α (22,23). Thus, a chain of specific protein-protein interfaces links unwinding of the parental strands to priming of nucleic acid synthesis on template DNA.…”
mentioning
confidence: 99%